Desain Generator Magnet Permanen RPM Rendah Dengan Memanfaatkan Motor Kipas - Nugroho, Sidik; , Ir. Jatmiko, M.T (2016)
Permanent magnet generator is one of electric machine that utilizes mechanical force to produce electricity generator which utilizes a permanent magnet as a rotor. This study discusses the design of a permanent magnet generator by using a fan and analyze the effect of the winding of the generator output. The fan used is the type of fan that uses a permanent magnet as the rotor. Redesign done by replacing the generator rotor permanent magnet type ferrite of a fan with a permanent magnet type neodymium magnet and as much as 6 magnet and using acrylic as his frame. Stator frame using the default fan frame 1 slot with the number of turns 4100. This generator is capable of producing a maximum output voltage at a frequency of 50 Hz 8,4v at a speed of 300 rpm, and the lowest voltage 3,5v at a speed of 100 rpm, at a frequency of 60 Hz the highest output voltage reaches 9,1v at a speed of 350 rpm. This generator is able to generate power of 12.194 mW at a speed of 350 rpm, the experiment was done in a lab scale, experimental results can be developed on a larger scale. In order to obtain a larger output power can change the number and size of turns, varying the neodymium permanent magnet of a certain size and narrowing the gap with the rotor and stator, in order to achieve greater power.